Virus surveys of process vegetable crops pea beetroot and dwarf bean - Fletcher, J.D.; Ziebell, H. (New Zealand Plant Protection, 2016)
In a survey of 14 processing crops and 7 pea seed crops throughout Canterbury Cucumber mosaic virus (CMV) was the most widespread with crop incidences of up to 20 Alfalfa mosaic virus (AMV) up to 11 Pea seedborne mosaic virus (PSbMV) up to 9 Soybean dwarf virus (SDV) up to 2 Turnip yellows virus (TuYV) up to 2 and Bean yellow mosaic virus (BYMV) up to 35 Red clover vein mosaic virus (RCVMV) was detected in peas for the first time in New Zealand with incidences of up to 35 Pea necrotic yellow dwarf virus (PNYDV) Faba bean necrotic yellows virus (FBNYV) and Broad bean stain virus (BBSV) were not detected In a survey of 8 beetroot crops TuYV was detected in Auckland at 1 incidence but not in Hawkes Bay Beet mosaic virus was detected at 1 incidence in both regions Fungal leaf spotting pathogens appear a greater concern in beetroot In 12 dwarf bean processing crops throughout Canterbury virus was only detected in early sown crops AMV and RCVMV were most widespread with incidences of up to 9; CMV with up to 7 incidence; then BYMV TuYV and SDV each with 1 incidence No Bean common mosaic virus was detected